Evaluation of Handwriting Movement Kinematics: From an Ecological to a Magnetic Resonance Environment - Bisio, Ambra; Pedullà, Ludovico; Bonzano, Laura; Ruggeri, Piero; Brichetto, Giampaolo; Bove, Marco (Frontiers in Human Neuroscience, 2016)
Writing is a means of communication which requires complex motor, perceptual, and cognitive skills. If one of these abilities gets lost following traumatic events or due to neurological diseases, handwriting could deteriorate. Occupational therapy practitioners provide rehabilitation services for people with impaired handwriting. However, to determine the effectiveness of handwriting interventions no studies assessed whether the proposed treatments improved the kinematics of writing movement or had an effect at the level of the central nervous system. There is need to find new quantitative methodologies able to describe the behavioral and the neural outcomes of the rehabilitative interventions for handwriting. In the present study we proposed a combined approach that allowed evaluating the kinematic parameters of handwriting movements, acquired by means of a magnetic resonance-compatible tablet, and their neural correlates obtained simultaneously from a functional magnetic resonance imaging examination. Results showed that the system was reliable in term of reproducibility of the kinematic data during a test/re-test procedure. Further, despite the modifications with respect to an ecological writing movement condition, the kinematic parameters acquired inside the MR-environment were descriptive of individuals’ movement features. At last, the imaging protocol succeeded to show the activation of the cerebral regions associated with the production of writing movement in healthy people. From these findings, this methodology seems to be promising to evaluate the handwriting movement deficits and the potential alterations in the neural activity in those individuals who have handwriting difficulties. Finally, it would provide a mean to quantitatively assess the effect of a rehabilitative treatment.